Clinical impact of collagen sponge combined with substance P on maxillofacial trauma repair in rats - Wang, Qian; Zhang, Yong; Guo, Yan; Yang, Xiaolan (Frontiers in Medicine, 2025)
ObjectiveCollagen sponge and substance P (SP) can facilitate trauma healing. Therefore, this study aimed to clarify the role and mechanism of collagen sponge combined with SP in maxillofacial trauma healing.MethodsA maxillofacial trauma model was established using rats. The rats were divided into four groups: research group 1 (RG 1; Vaseline gauze and SP), research group 2 (RG 2; Vaseline gauze and collagen sponge), research group 3 (RG 3; collagen sponge and SP), and a control group (CG; Vaseline gauze and normal saline). The trauma healing rate was examined on days 3, 7, and 14 after treatment, and the pathological morphology of the trauma was examined on day 14 after treatment. Hydroxyproline expression; positive expression of basic fibroblast growth factor (bFGF); serum IL-6 and TNF-α levels; matrix metalloprotease-9 (MMP-9) and tissue inhibitor of metalloproteinase-1 (TIMP-1) protein levels; and vascular endothelial growth factor (VEGF), TGF-β1, and SMAD3 mRNA levels were detected on day 14 after treatment.ResultsOn days 7 and 14 after treatment, the trauma healing rates in all research groups were higher than that in the CG, and the trauma healing rate in RG 3 was higher than that in RG 1 and RG 2. On day 14 after treatment, compared to the CG, the number of inflammatory cells in the rat trauma tissues was reduced in all research groups, while the collagen fiber content was enhanced in all research groups. Compared to RG 1 and RG 2, the number of inflammatory cells in RG 3 was lower, while the collagen fiber content in RG 3 was higher. The tissue hydroxyproline and bFGF levels in all research groups were higher than those in the CG, and the levels in RG 3 were higher than those in RG 1 and RG 2. Compared to the CG, serum levels of IL-6 and TNF-α and tissue levels of MMP-9 were lower across all research groups, while tissue levels of TIMP-1 were elevated in all research groups. The improvements in serum IL-6 and TNF-α levels and tissue MMP-9 and TIMP-1 levels in RG 3 were greater than those in RG 1 and RG 2. Compared to the CG, the mRNA levels of VEGF, TGF-β1, and SMAD3 were higher in all research groups, with RG 3 showing higher levels than RG 1 and RG 2.ConclusionCollagen sponge and SP can facilitate the healing of maxillofacial trauma and reduce scar formation after trauma healing. This effect may be related to the TGF-β1/Smad3-VEGF signaling pathway.